2022
DOI: 10.3389/fgene.2022.891744
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of an m6A Modification of JAK-STAT Signaling Pathway–Related Prognostic Prediction Model in Gastric Cancer

Abstract: Background: Gastric cancer (GC) is one of the malignant tumors worldwide. Janus (JAK)–signal transduction and activator of transcription (STAT) signaling pathway is involved in cellular biological process and immune function. However, the association between them is still not systematically described. Therefore, in this study, we aimed to identify key genes involved in JAK-STAT signaling pathway and GC, as well as the potential mechanism.Methods: The Cancer Genome Atlas (TCGA) database was the source of RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…46 However, there is still little research to explore the impact and mechanism of m 6 A modi cation of JAK-STAT pathway members on the occurrence and development of GC. 47 Herein, our research provides evidence that METTL3-mediated m 6 A modi cation of STAT5A increases the stability and expression of STAT5A. Moreover, STAT5A exerts an oncogenic role in GC by promoting cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 66%
“…46 However, there is still little research to explore the impact and mechanism of m 6 A modi cation of JAK-STAT pathway members on the occurrence and development of GC. 47 Herein, our research provides evidence that METTL3-mediated m 6 A modi cation of STAT5A increases the stability and expression of STAT5A. Moreover, STAT5A exerts an oncogenic role in GC by promoting cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, it has been suggested that decreased METTL3 expression increases SOCS stability, thereby inhibiting IL7-STAT5 signaling pathway activation, which further leads to abnormalities in T-cell proliferation and differentiation [47]. However, few studies have explored the role and mechanism of the m 6 A modification of JAK-STAT pathway members on the occurrence and development of GC [48]. Our research provides evidence that METTL3-mediated m 6 A modification of STAT5A increases the stability and expression of STAT5A.…”
Section: Discussionmentioning
confidence: 99%